DEVELOPING A MODEL OF PROFESSIONAL IDENTITY IN MEDICAL STUDENTS: THE ROLE OF MOTIVATION AND PARTICIPATION - Yoga Pamungkas Susani; Gandes Retno Rahayu; Rossi Sanusi; Yayi Suryo Prabandari; Harsono Mardiwiyoto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: It is very important to develop professional identity among medical students, as it will affect how they work in the future. Factors affecting professional identity in medical education context need to be explored. This study aimed to develop a model of professional identity in medical students which examine the role of motivation, self-efficacy, personal reflection, social interaction, curriculum in action perceived by students and participation in determining professional identity. Methods: A cross-sectional survey was conducted among medical students in Mataram University. A total of 303 pre-clinical (year 1 to 4) and clinical students (year 5 to 6) filled out the questionnaires. Partial least square - structural equation model analysis was performed.Results: The modification model had a good model fit (GoF 0.404). The average path coefficient was 0.303 (p<0.001) and the adjusted average R square was 0.321 (p<0.001). Forty percent of variance in professional identity could be explained by motivation (β=0.51, p<0.001, f2=0.281) and participation (β=0.32, p<0.001, f2=0.118).Conclusions: Motivation and participation of medical students may influence the professional identity. Based on the model, within the medical education processes, academic motivation of students should be maintained and fostered and participation should be supported.